2021
DOI: 10.1029/2021gl093370
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Sea Interaction in the Western Tropical Pacific and its Impact on Asymmetry of the Ningaloo Niño/Niña

Abstract: Ningaloo Niño/Niña is the dominant interannual sea surface temperature (SST) variability off Western Australia with the former typically stronger than the latter. Although a recent study suggested that oceanic teleconnections from the Pacific partly contribute to the amplitude asymmetry, this seems counterintuitive as La Niña, which often induces the Ningaloo Niño, is generally weaker than El Niño. Here, mechanisms of the amplitude asymmetry in the oceanic teleconnection are investigated by analyzing reanalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Statistics have shown that El Niño events significantly affect summer monsoon rainfall, zonal wind anomalies and the following summer SST anomaly (SSTA) over the IO, but La Niña events do not (Ihara et al, 2007;Wu et al, 2021). Kusunoki et al (2020Kusunoki et al ( , 2021 reported that the impact of La Niña on Ningaloo Niño-related SSTA off western Australia is stronger than that of El Niño due to the stronger oceanic teleconnections from the Pacific. Several studies have also provided insights into the significant modulation of specific segments of the SSTC and their associated meridional heat transport by the ENSO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics have shown that El Niño events significantly affect summer monsoon rainfall, zonal wind anomalies and the following summer SST anomaly (SSTA) over the IO, but La Niña events do not (Ihara et al, 2007;Wu et al, 2021). Kusunoki et al (2020Kusunoki et al ( , 2021 reported that the impact of La Niña on Ningaloo Niño-related SSTA off western Australia is stronger than that of El Niño due to the stronger oceanic teleconnections from the Pacific. Several studies have also provided insights into the significant modulation of specific segments of the SSTC and their associated meridional heat transport by the ENSO.…”
Section: Introductionmentioning
confidence: 99%
“…Kusunoki et al. (2020, 2021) reported that the impact of La Niña on Ningaloo Niño‐related SSTA off western Australia is stronger than that of El Niño due to the stronger oceanic teleconnections from the Pacific. Several studies have also provided insights into the significant modulation of specific segments of the SSTC and their associated meridional heat transport by the ENSO.…”
Section: Introductionmentioning
confidence: 99%